IbM Kelompok Petambak Tradisional Udang Windu Di Desa Kedung Peluk, Yang Menghadapi Penurunan Hasil Panen Secara Drastis Sejak Tahun 1994 [IbM For Windu Shrimp Small Scale Farmer Traditional In Kedung Peluk Village Whose Gets Harvesting Decreased Since 1994 ] - Gunanti Mahasri; A. Shofy Mubarak; Sudarno Sudarno (Faculty of Fisheries and Marine Universitas Airlangga, 2011)
Abstract Tiger shrimp (Penaeus monodon Fab) is one of the economically important shrimp, until 1992 became the most important of non petroleum export commodity from fishery sector. Since the end of 1993 up to now, the Penaeus monodon Fab death level has been relatively high and due to this circumstance have been caused many ponds collapsed so that the shrimp production was dramatically declined for year by year. Candi District is one of the Sidoarjo Region areas which have big fisheries potential, aspecially for the breakist water pond, that the topest as the other district. There are a lot of shrimp dead cases until now. But, so that 80% of breakist water pond were broken and not operational. The objective of this societies service activities is applicated a new shrimp culture technology with traditional plus Imuno-Biocirculation System. Imuno-Biocirculation System (SIBR) for increases the shrimp harvest at Candi District Region of Sidoarjo, at June until November 2011. The method using in the activity were socialitation/counseling, dempond and guiding to application of the SIBR model in one periode. Monitoring and evaluation about this result were done in one month after the activity ending. This result showed that a positive indication. There was the knowledges of the farmer in ceases by socialization, it also applicated a model in the right method for shrimp culture. There were also showed that the SIBR model can in ceased the shrimp harvest from 272,43 kg/ha to 854,66 kg/ha, it means was increased 313%. The conclution of this activity is the SIBR model can increased the shrimp harvest and can applicates in more larges area in Sidoarjo Region.